Hubungan Beban Kerja Dengan Stres Kerja Dosen di STIKes Senior Medan - Manullang, Agustinus; Faadhil, Faadhil (Universitas Medan Area, 2024)
This research aims to determine the relationship between workload and work stress of Medan Senior STIKes lecturers. The method in this research uses quantitative methods. The population in this study were Senior Medan STIKes lecturers. The sample in the study amounted to 60 people. The sampling technique uses total sampling. The data collection method uses a workload scale and work stress scale with a Likert scale model. The data analysis method uses Person Product Moment. The results of this study show that there is a positive relationship between workload and work stress of lecturers at STIKes Senior Medan, with a correlation coefficient rxy = 0.448, which shows a strong relationship. The linear significant value is 0.563 with p = 0.000 (p 0.05), which means there is a linear relationship between workload and work stress. The higher the workload, the higher the work stress. This research hypothesis is accepted. Most of the Medan Senior STIKes lecturers have moderate levels of work stress, with 41 lecturers (68.3% of all lecturers) experiencing moderate stress.